Pathways to Successful Transformation of Basic Education amid Educational Crises: A Case Study of the Experiments in Educational Reform by 271 Education Group - Hua, Mengyuan (Science Insights Education Frontiers, 2022)
The 2021 release of Reimagining Our Futures Together: A New Social Contract for Education by the United Nations Educational, Scientific, and Cultural Organization was a reaction to a number of serious problems discovered in worldwide educational reforms. It sought to establish a new social compact for education to fulfill its unmet promise in the face of many educational crises and to combat future uncertainty. Using the methods of 271 Education Group as a case study, this article examines China’s efforts to transform basic education in response to widespread educational issues and how they have represented the major principles espoused by the UNESCO report. The article elaborates on the coping strategies of 271 Education Group, such as incorporating eco-civilization education into basic schooling, constructing life-based curricula that are built on knowledge commons, introducing pedagogy rooted in cooperation and solidarity, and promoting teacher professional development through collaborative educational research.